151k views
4 votes
PLEASE HELP ME!!! ASAPPPPP!!!!!!


expand and simplify​

PLEASE HELP ME!!! ASAPPPPP!!!!!! expand and simplify​-example-1
User Vkt
by
5.2k points

1 Answer

2 votes

Answer:

8x+11

Explanation:

This problem can be solved by using distributive property.

if there is expression a(b + c).

then by distributive property.

a(b + c). = ab + ac

given problem

3(2x+1) + 2(x+4)

by using distributive property.

=>3*2x + 3*1 + 2*x + 2*4

=> 6x + 3 + 2x + 8

adding term containing x together and constant term together

=> 8x + 11

Thus, solution is 8x+11

User Ohadinho
by
5.3k points